(untitled) (Biological Sciences - PJSIR, 2009)
Experiment for finding the effect of pre-soaking of wheat seeds varieties, viz Wafaq-2001 and Punjab-96, in salicylic acid (SA) solution on the drought tolerance of wheat, revealed increase in the total biomass and grain yield per plant as well as in spikes per plant, 100 seed weight, proline, total soluble sugars, membrane stability index (MSI), superoxide dismutase (SOD) and ascorbate peroxidase (APOX) activity in both the tested varieties. The yield increase in drought tolerant variety Wafaq-2001 was more as compared to drought sensitive Punjab-96. Results signify the role of SA in regulating the drought response of wheat and that SA could be seed primed and used as a potential growth regulator under drought stress conditions.